Respuesta :

a. (f+g)(x) = 8x+2

b. (f-g)(x) = 4x-6

Step-by-step explanation:

Given

[tex]f(x) = 6x-2\\and\\g(x)=2x+4[/tex]

a. (f+g)(x)

[tex](f+g)(x)=f(x)+g(x)\\=6x-2+(2x+4)\\=6x-2+2x+4\\=6x+2x-2+4\\=8x+2[/tex]

b. (f-g)(x)

[tex](f-g)(x)=f(x)-g(x)\\=(6x-2)-(2x+4)\\=6x-2-2x-4\\=6x-2x-2-4\\=4x-6[/tex]

Hence,

a. (f+g)(x) = 8x+2

b. (f-g)(x) = 4x-6

Keywords: Functions

Learn more about functions at:

  • brainly.com/question/5282516
  • brainly.com/question/5424148

#LearnwithBrainly

ACCESS MORE